Ac–dc Serial-interleaved Boost Converter Applied In A Single-stage Pfc - Postiglione, Cícero S.; Fuerback, André L.; Nascimento, Claudinor B.; Martins, Denizar C.; Perin, Arnaldo J. (Eletrônica de Potência, 2013)
This paper presents single-stage power factor corrected (PFC) AC–DC converters based on a modified serial-interleaved boost converter. The topologies are a composition of a modified interleaved boost converter with a DC–DC converter. The interleaving allows each boost converter to operate in discontinuous conduction mode (DCM) while still having continuous conduction mode (CCM) input current. High power factor and reduced current ripple are obtained, meeting IEC 61000-3-2 regulations for wide load range. The converters also operate with zero voltage switching (ZVS) resulting in high efficiency. The steady-state analysis of the converter is performed along with the description of the converter operation stages. Finally, a simplified design procedure is proposed, from where a prototype is designed and built. Finally experimental results from a laboratory prototype are presented.